“Implementación de un sistema inalámbrico de monitoreo florícola (dataroses) para el mejoramiento de la productividad en la Compañía Tamboroses S.A., ubicada en la parroquia Mulaló, cantón Latacunga”. - Caisaguano Moreno, Johana Enriqueta (2007)
The TAMBOROSES S.A. company begins its activities of production of roses from 1.994, located in the Mulalo parish, city of Latacunga, province of Cotopaxi, it is a farm of roses, that thanks to the work of its administrative personnel, technical personnel and of field it has been growing day to day until becoming in one of the main farms of exporting roses of the country. The implementation of the Wireless System Monitoring of Roses, for the improvement of productivity in the company TAMBOROSES S.A., has great reception by staff working on the farm for their different applications.